PERAN SUPERVISI AKADEMIK DALAM MENINGKATKAN KUALITAS EVALUASI KINERJA GURU PADA PROSES PEMBELAJARAN DI SEKOLAH DASAR - Eka Wahyuni; Yari Dwikurnaningsih; Herry Sanoto (STKIP Subang, 2026)
Academic supervision is one of the efforts that can be implemented to improve the quality of learning through the professional development of teachers. This study aims to analyze the role of academic supervision in improving the quality of teacher performance evaluation in the learning process at elementary schools. This research employed a descriptive qualitative approach with the school principal and teachers as the research subjects. Data were collected through observation and interviews, while the data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that academic supervision is carried out systematically through the stages of pre-observation, classroom observation, and post-observation. The supervision process provides feedback to teachers in planning instruction, developing assessment instruments, and reflecting on the learning process. Academic supervision also assists teachers in improving the quality of learning evaluation, enabling assessments to be conducted more systematically and in accordance with learning objectives. In addition, the continuous implementation of supervision encourages teachers to be more open to feedback and to continuously improve their teaching practices. In conclusion, academic supervision plays an important role in improving the quality of teacher performance evaluation and supporting the improvement of learning quality in elementary schools.